Kinerja Rantai Pasok Industri Kopi Bubuk di Kecamatan Kemiling Kota Bandar Lampung - Riantini, Maya; Affandi, Muhammad Irfan; Nur’aini, Lestari Gita; Kusnandi, Savira Adelia (Jurnal Penelitian Pertanian Terapan, 2023)
This study aims to analyze supply chain flow patterns and supply chain performance of ground coffee agro-industry in Kemiling District, Bandar Lampung City. The census method was used in this study, by taking all five ground coffee agroindustry in the Kemiling District, Bandar Lampung City. Respondents in this study were agro-industry owners, coffee farmers, collectors, wholesalers, retailers, and ground coffee consumers. The sampling technique for supply chain respondents uses the snowball sampling method. Research data collection was carried out from January to February 2022. The data analysis used was descriptive qualitative and quantitative methods. The results showed that overall, product flow, money flow, and information flow that occurred in the supply chain were running well. Several performance indicators for the supply chain of farmers are below the parity value, while the performance of the supply chain traders and agro-industry are all at the superior and advantage criteria.